2003
DOI: 10.1046/j.1365-2265.2003.01859.x
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnoea syndrome impairs insulin sensitivity independently of anthropometric variables

Abstract: Obese patients with obstructive sleep apnoea syndrome are more insulin resistant than patients with simple obesity independently of the degree and distribution of adiposity. The worsening in insulin sensitivity in obstructive sleep apnoea syndrome patients could reflect the hypoxic state and would account for the increased vascular risk in this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
3
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(49 citation statements)
references
References 30 publications
5
37
3
4
Order By: Relevance
“…Similar data have been obtained in samples of OSA patients (tables 3 and 4) [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80], with a large prevalence of positive [63,[64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] rather than negative [78][79][80] studies. In clinical populations, OSA patients characterised by full-PSG were significantly more likely to have impaired glucose tolerance (IGT) and diabetes than subjects free of OSA syndrome (OSAS) [71].…”
Section: Physiological and Clinical Datasupporting
confidence: 65%
“…Similar data have been obtained in samples of OSA patients (tables 3 and 4) [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80], with a large prevalence of positive [63,[64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] rather than negative [78][79][80] studies. In clinical populations, OSA patients characterised by full-PSG were significantly more likely to have impaired glucose tolerance (IGT) and diabetes than subjects free of OSA syndrome (OSAS) [71].…”
Section: Physiological and Clinical Datasupporting
confidence: 65%
“…Several studies have reported on the relationship between OSA and glucose metabolism [2,3,5,25,26,28,29]. The prevalence of OSA in our cohort was higher than the prevalence reported in the Wisconsin Sleep Cohort Study [4].…”
Section: Discussioncontrasting
confidence: 53%
“…mostraram que os pacientes com SAOS (n = 30) apresentam menor sensibilidade à insulina, calculada pelo ISI, do que o grupo controle sem AOS (n = 27), mesmo após ajuste para idade, IMC e relação cintura-quadril (21).…”
Section: Resistência à Insulina (Ri) E Saosunclassified